IMPLEMENTATION OF DOUBLE CRITICAL TECHNOLOGY SOCIETY LEARNING MODEL FOR MIDDLE SCHOOL STUDENTS - Ivan Eldes Dafrita (Indonesian Journal of Science and Education (IJOSE), 2020)
This study aims to determine the implementation of Double Critical Technology Society (DCTS) learning model on the critical thinking skills of 7th grade students of SMP Negeri 1 Suhaid. This type of research is a quasi-experimental with posttest only design. Samples were taken from 7th grade students of SMP Negeri 1 Suhaid in the first semester of the 2019/2020 Academic Year which consisted of two classes, namely the experimental class and the control class. The research instruments used were a test to measure students' critical thinking skills after DCTS learning model was applied and a questionnaire to measure student responses after being given a DCTS learning model. The data obtained were then analyzed using descriptive statistics and independent sample t test. The results of data analysis with the independent sample t test showed that the significance value of students 'critical thinking skills was 0.00 less than 0.05 so there was an influence on the implementation of the DCTS learning model on students' critical thinking skills. The critical thinking skills of the experimental class students with an average value of 71.30 were better than the control class which had an average value of 50.23. The results of the assessment of the response questionnaire with an average of 83.25 showed an excellent response from students to the DCTS learning model.